Protocol for a pilot, randomised, double-blinded, placebo-controlled trial of prophylactic use of tranexamic acid for preventing postpartum haemorrhage (TAPPH-1). Issue 10 (11th October 2017) - Alam, Asim; Bopardikar, Ameya; Au, Shelly; Barrett, Jon; Callum, Jeannie; Kiss, Alex; Choi, Stephen
Abstract : Introduction: Postpartum haemorrhage (PPH) is the leading cause of maternal morbidity and mortality worldwide. Despite the availability of multiple uterotonic agents, the incidence of PPH continues to rise. Tranexamic acid (TXA) has been shown to be a safe, effective and inexpensive therapeutic option for the treatment of PPH, however, its use prophylactically in mitigating the risk of PPH is unknown. This pragmatic randomised prospective trial assesses the feasibility and safety of administering TXA at the time of delivery for the prevention of PPH. Methods and analysis: A pilot pragmatic randomised double-blinded placebo-controlled trial will be performed. 58 singleton parturients at term >32 weeks, undergoing either spontaneous vaginal delivery, or caesarean section will be randomised to receive 1 g of TXA or placebo (0.9% saline) intravenously. The primary outcome assessed will be the feasibility of administrating TXA, along with collecting data regarding safety of drug administration. The groups will also be analysed on efficacy of mitigating the onset of PPH and clinically relevant variables. Demographic, feasibility, safety and clinical endpoints will be summarised and the appropriate measures of central tendency and dispersion will be presented. Ethics and dissemination: This protocol was approved by the Sunnybrook Health Sciences Centre Research Ethics Board (number: 418-2016). The results will be disseminated in a peer-reviewed journal and at scientific meetings. Trial registration number: NCT03069859 ; Pre-results.